Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Indonesia - Annisa Nanda Selvira; Thomas Andrian (Departement of Mathematics Education, 2024)
Unemployment is a condition where people of productive age do not have work. Unemployment is still a problem that is often faced by both developing and even developed countries. Because the unemployment rate is still used as a measure of success in a country's economic development, by looking at the unemployment rate you can also see whether or not a country's level of prosperity has been achieved. The aim of this research is to see the influence of the Human Development Index, Minimum Wage, and Investment, both Foreign Investment and Domestic Investment. The data used is panel data from 5 sample provinces in Indonesia spanning the years 2011 to 2022. The results of this research show that the Human Development Index and Foreign Investment have a negative and significant influence on the Open Unemployment Rate in Indonesia. Meanwhile, Regional Minimum Wages and Domestic Investment have a positive and significant influence on the Open Unemployment Rate in Indonesia.